Community Perception of the Deradicalization and Rehabilitation Program for Surrendered Insurgents in Malam Sidi Camp, Gombe State - Sati, Sheikh Kubenubu; Mshelia, Ishaku Yakubu; Ndubuisi, Adigwe Austin (Kashere Journal of Politics and International Relations, 2025)
Most often issues of public concern and safety are met with solutions from government through government formulated policies. These policies seek to address issues around public safety especially protection of lives and property. One of such government policy on violent extremism is the creation of a deradicalization and rehabilitation camp in Malam Sidi in Gombe State. This paper addresses the perspective of what those who are affected by the policy think about government’s solution to the problem of violent extremism. Using key informant interviews and purposeful sampling, the paper discovered that the public knows little to nothing about what goes on the camp where the deradicalization and rehabilitation of surrendered insurgents is taking place. The work is guided by the system theory and recommends that policies that seek to resolve issues need to be accepted by the people it directly affects. Therefore, the government needs to realign the drawing board to include the community members in the processes of decentralizing and rehabilitation these surrendered violent extremist